2021
DOI: 10.17222/mit.2021.222
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF DIFFRENT LOADS ON THE WEAR BEHAVIORS OF 5Cr5Mo2V STEEL AT 700 °C

Abstract: The effect of different loads on the high-temperature wear behavior of 5Cr5Mo2V steel at 700 °C was investigated. Wear morphologies, oxide compositions and matrix evolution were studied. The results showed that the wear rate increased with an increased test load, and the wear mechanism transformed from abrasive-oxidative wear to adhesive-oxidative wear. The relation between a delaminated oxide layer and cracks in the matrix were investigated. The exfoliation of carbides and displacement difference between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The plastic deformation of subsurface contributed to the formation of tribological layer, the wear behaviour was affected by oxides and subsurface deformation [15]. It is generally accepted that wear resistance of the different microstructures depends on thermal stability, toughness and plastic deformation resistance, especially the microstructure change and energy consumption during sliding [16][17][18]. By comparing the wear characteristics of austenitic stainless steel and austenitic-ferritic stainless steel, Straffelini [15] found that the low ductility can delay wear transformation (delamination→tribo-oxidation) in austenitic-ferritic stainless steel.…”
Section: Introductionmentioning
confidence: 99%
“…The plastic deformation of subsurface contributed to the formation of tribological layer, the wear behaviour was affected by oxides and subsurface deformation [15]. It is generally accepted that wear resistance of the different microstructures depends on thermal stability, toughness and plastic deformation resistance, especially the microstructure change and energy consumption during sliding [16][17][18]. By comparing the wear characteristics of austenitic stainless steel and austenitic-ferritic stainless steel, Straffelini [15] found that the low ductility can delay wear transformation (delamination→tribo-oxidation) in austenitic-ferritic stainless steel.…”
Section: Introductionmentioning
confidence: 99%